Dystopias of Tyranny and Misogyny: The Handmaid’s Tale and The Carhullan Army - Kübra Baysal (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Displaying the probable future and the doom of humanity and the Earth, Margaret Atwood’s The Handmaid’s Tale (1985) and Sarah Hall’s The Carhullan Army (2007) are two dystopian novels that present the terrible state of women along with the degradation of the society and the nonhuman environment. Atwood’s the Republic of Gilead and Hall’s the Authority enforce an extremely oppressive, exploitative, and misogynist order on women, which corrupts the natural flow of daily life and destroys the human and nonhuman spheres. Depicting the resistance of women against tyranny through female protagonists, these novels picture dystopian worlds of chaos and destruction ruled by anthropocentric and patriarchal dictate. With this perspective, this article aims to discuss the problem of patriarchal oppression on women in dystopian societies as portrayed in The Handmaid’s Tale and The Carhullan Army from the perspectives of the feminist and ecofeminist theories.